Effectiveness of a Structured Teaching Programme on Knowledge and Attitude Regarding the Causes, Transmission, and Prevention of Sexually Transmitted Infections Among Rural Women in the Field Practice Area of RHTC, Yadwad, Dharwad District - Archana Jadav (International Journal of Women's Health Nursing And Practices, 2025)
Sexually Transmitted Infections (STIs) pose serious long-term health risks, particularly for women and newborns. Women in rural areas often face significant social consequences due to inadequate STI awareness, which can lead to unsafe sexual practices. This study aimed to assess the knowledge and attitudes of rural women aged 15 to 49 years regarding the causes, transmission, and prevention of selected STIs in the RHTC Yadwad field practice area. Additionally, the study sought to evaluate the effectiveness of a Structured Teaching Program (STP) and explore associations between sociodemographic variables and STI knowledge and attitudes. A quantitative research approach with a one-group pretest-post-test quasi-experimental design was used. Sixty rural women were selected using a structured knowledge questionnaire and attitude scale. Following the pretest, participants received a Structured Teaching Program on STIs. The post-test was administered on the seventh day using the same tool. Data were analysed using descriptive and inferential statistics. The results showed a significant improvement in both knowledge and attitude scores after the intervention. The mean post-test knowledge score was 16.5, while the mean attitude score was 29.88. A statistically significant improvement was observed at the 5% level (P
Keywords: Rural women; STP; cause; spread and prevention